2022
DOI: 10.1371/journal.pone.0276156
|View full text |Cite
|
Sign up to set email alerts
|

Does head and cervical posture correlate to malocclusion? A systematic review and meta-analysis

Abstract: Background The association of head and cervical posture with malocclusion has been studied for many years. Despite extensively encouraging researches, no conclusive evidence has been reached for clinical application. Objective To identify the question “Does head and cervical posture correlate to malocclusion?”, a systematic review and meta-analysis based on the available studies were carried out (PROSPERO registration number: CRD42022319742). Methods A search of PubMed, Embase, Cochrane Library, and the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…This review also points out that there is not enough scientific evidence to prove a cause-effect relationship. A further review confirms that the existing literature is not sufficient to prove the relationship between head and cervical posture and sagittal malocclusion [ 16 ].…”
Section: Introductionsupporting
confidence: 55%
“…This review also points out that there is not enough scientific evidence to prove a cause-effect relationship. A further review confirms that the existing literature is not sufficient to prove the relationship between head and cervical posture and sagittal malocclusion [ 16 ].…”
Section: Introductionsupporting
confidence: 55%
“…A study has shown a high prevalence of head posture deviation ( Batistão et al, 2016 , Verma et al, 2018 ). Muscle imbalance consequential to myofunctional disorders is often considered to cause abnormalities in teeth and jawbone positions ( Peng et al, 2022 ). This can negatively affect the skeletal system, specifically the alteration of facial morphology ( Garg et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The development of the dentofacial complex is influenced by muscle balance in the craniofacial region. Muscle imbalance consequential to myofunctional disorders is often considered to cause abnormalities in the teeth and jawbone positions, notably in cases involving oral breathing, lip sucking, and tongue thrusting ( Peng et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…or undergoing several sessions of analytical and symptomatic physiotherapy or osteopathy, fail to fully recover; because they have dismissed a possible cause or effect: Malocclusion. 1,2 If the etiology of the problem is not meticulously investigated, the symptoms recur and soon after cause the individual to become ill, presenting acute and chronic symptoms. 3 Some confusion surrounds professionals when it comes to determining where (postural sensors: eyes, mouth and feet) is the primary imbalance and what is the most appropriate therapy for its restoration.…”
Section: Short Communicationmentioning
confidence: 99%